Experimental Study on Characteristics of Seismic Damage and Damping Technology of Absorbing Joint of Tunnel Crossing Interface of Soft and Hard Rock - Dao-yuan Wang; Jin-xiu Yuan; Guang-yao Cui; Jia Liu; Hong-fan Wang (Shock and Vibration)
It has generally been believed that the serious seismic damage of tunnel mainly occurred in portal section and fault dislocation zone. However, the survey of seismic damage showed that the seismic damage of tunnel also mainly occurred in geological section at interface of soft and hard rock. Currently, merely scholars have made some research studies on characteristics of seismic damage and damping technology of tunnel crossing the vertical interface between soft and hard rock in high intensity area, and the mechanism of seismic damage has not been clearly revealed. Therefore, based on the Urumqi Metro Tunnel project in China, a three-dimensional six-degree-of-freedom shaking table model test was carried out. Through comparative analysis of peak ground acceleration (PGA), displacement difference at the interface between soft and hard rock, and structural safety factor under 5 kinds of conditions, the seismic damage characteristics of tunnel crossing interface of soft and hard rock were revealed, and a new damping technology of absorbing joint was proposed. The following findings can be drawn. (1) The seismic damage of tunnel is mainly affected by stratum inertial force under the homogeneous stratum of soft rock. The seismic damage of tunnel is mainly caused by the forced displacement (the displacement difference between the two sides of interface of soft and hard rock), followed by stratum inertial force under the geological condition of interface between soft and hard rock. (2) The conventional type of absorbing joint (only the second lining is set with absorbing joint) is used in tunnel lining structure, and the damping ratios of principal tensile stress, bending moment, and axial force of lining are above 47.5%, 40.7%, and 72.7%, respectively. Compared with conventional type of absorbing joint, the damping effect of new type of absorbing joint (staggered absorbing joints of primary support and secondary lining) is 19.9% higher than that of conventional type. (3) The new type of absorbing joint is recommended for tunnel crossing interface section of soft and hard rock. The specific implementation suggestions are as follows: the setting interval of second lining absorbing joint is the same as the length of lining formwork trolley, and the interval of primary support absorbing joint can be set according to excavation footage length. The filling materials in second lining absorbing joint can be shared with the rubber waterstop set in construction joint, and the primary support absorbing joint can be realized by injecting mixtures of rubber particles and shotcrete.